The indignities of shielding during the COVID-19 pandemic for people with sickle cell disorders: an interpretative phenomenological analysis - Berghs, Maria; Horne, Francesca; Yates, Scott; Kemp, Rachel; Webster, Amy (Frontiers in Sociology, 2024)
This paper seeks to understand the first-hand experiences of people with sickle cell, a recessively inherited blood disorder, who were identified as clinically extremely vulnerable during the COVID-19 pandemic. Part of a larger sequential mixed methods study, this paper uses a selective sample of eight qualitative semi-structured interviews which were analysed using Interpretative Phenomenological analysis (IPA). A first stage of IPA analysis focused on practical concerns participants had correlated to understanding shielding and their feelings about being identified as clinically extremely vulnerable. In a secondary stage of analysis, we examined the emotions that it brought out and the foundations of those based on discriminations. This paper adds to our theoretical understandings of embodiment and temporality with respect to chronicity and early aging. It explains how people with sickle cell have an embodied ethics of crisis and expertise. It also elucidates how people's experiences during the pandemic cannot be seen in void but illustrate ableism, racism and ageism in society writ large.